2016
DOI: 10.1371/journal.pone.0144570
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors and Risk Mapping for Rift Valley Fever Epidemics in Kenya

Abstract: BackgroundTo-date, Rift Valley fever (RVF) outbreaks have occurred in 38 of the 69 administrative districts in Kenya. Using surveillance records collected between 1951 and 2007, we determined the risk of exposure and outcome of an RVF outbreak, examined the ecological and climatic factors associated with the outbreaks, and used these data to develop an RVF risk map for Kenya.MethodsExposure to RVF was evaluated as the proportion of the total outbreak years that each district was involved in prior epizootics, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 18 publications
(20 reference statements)
0
44
2
Order By: Relevance
“…This could be attributed to the ecological differences between the regions as well as the diversity of potential vector species. Previous studies have also reported low numbers of arbovirus cases in Isiolo relative to Tana-River [5, 12]. In previous arbovirus surveys conducted in neighboring Garissa county, WNV, Semliki Forest virus and Ndumu virus, traditionally known to be mosquito-borne, were detected in ticks taken off cattle and other wild animals [32] suggesting that although these viruses have traditional reservoirs and vectors which have been documented, they may infect other animal species from which mosquitoes such as Ae .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…This could be attributed to the ecological differences between the regions as well as the diversity of potential vector species. Previous studies have also reported low numbers of arbovirus cases in Isiolo relative to Tana-River [5, 12]. In previous arbovirus surveys conducted in neighboring Garissa county, WNV, Semliki Forest virus and Ndumu virus, traditionally known to be mosquito-borne, were detected in ticks taken off cattle and other wild animals [32] suggesting that although these viruses have traditional reservoirs and vectors which have been documented, they may infect other animal species from which mosquitoes such as Ae .…”
Section: Discussionmentioning
confidence: 97%
“…Tana-River was more affected with16 human cases than Isiolo that only reported 7 probable cases [5, 12]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations